A Study on the Influence of Effective Structures on Agriculture Graduates’ Tendency Towards Cooperative Activities in Southern Khorasan Cooperation Sector - M Orangi; Gh.h Hosseininia; A Heydari (تعاون و کشاورزی, 2010)
Employment & unemployment are among the main issues in economy, as increasing employment & decreasing unemployment rate are one of the most important factors of development in any society. This is ever more important in the issue of employment of university graduates. Specialized agricultural cooperatives as partnership organizations have remarkable potential in quantitative and qualitative improvement of agri-products as well as entrepreneurship for graduates of agriculture. As a result, development of these cooperatives seems to be a necessity. In the current study, the tendency of agriculture graduates towards participation in cooperative sector has been investigated to study the causes of their inclination towards joining this section. This study is a descriptive-analytic research and correlative and cooperative methods have been used. The subject group consist of 200 persons were selected according to proportional random sampling method out of graduates and senior students of agriculture in the academic year 2008-09 and data was collected by questionnaires. Spss 11.5 computer program was used to process both descriptive and analytic data. The most important result of the descriptive approach was that nearly half of the subjects’ tendency towards cooperatives was moderate. The correlative analysis showed that the tendencies of the subjects for employment in cooperative section are significantly affected by their knowledge and awareness, incentives, barriers, educational needs, and age. Knowledge and incentives have positive effect on employment in this section while age, barriers and educational needs have negative impact. In addition, significant differences exist among subjects’ approaches from different universities, genders, as well as being student or graduate.